2015
DOI: 10.1002/ccd.26310
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous carotid artery access in infants < 3 months of age

Abstract: Our experience suggests that percutaneous CA access in infants <3 months of age is safe and feasible with preserved vascular patency and no neurological adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
2
35
0
1
Order By: Relevance
“…Hence, CA and even axillary artery (AA) access have been employed to place the PDA stent in some infants with this PDA anatomy. There are limited studies describing outcomes following surgical‐assisted or percutaneous CA access for neonatal interventions . These studies suggest that percutaneous CA is a safe alternative to traditional FA access, with a higher arterial patency rate post‐procedure compared with contemporary results from the FA .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, CA and even axillary artery (AA) access have been employed to place the PDA stent in some infants with this PDA anatomy. There are limited studies describing outcomes following surgical‐assisted or percutaneous CA access for neonatal interventions . These studies suggest that percutaneous CA is a safe alternative to traditional FA access, with a higher arterial patency rate post‐procedure compared with contemporary results from the FA .…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that CA access in children for cardiac catheterization is safe . The patency rate immediately following CA access was reported in two separate studies to be >95%.…”
Section: Discussionmentioning
confidence: 91%
“…In that series 40/42 patients had a normal CA noted by ultrasound performed within 24 hr of PCA, with two cases of mild CA stenosis. Another study by Choudhry et al found that in infants <3 months of age, PCA was associated with favorable acute results . However, the late and midterm outcomes following PCA remain unreported.…”
Section: Introductionmentioning
confidence: 99%
“…For PDAs that originate from the underside of the aortic arch (and some from the head/neck vessels), percutaneous axillary artery or common carotid artery access facilitates a direct and straight trajectory which allows for easier maneuverability of guidewires/stent systems. While previously axillary artery or common carotid artery access was performed via surgical cut down techniques, percutaneous axillary and percutaneous carotid artery access for PDA stenting has been shown to be safe and effective . We perform percutaneous axillary (Figure ) and percutaneous carotid artery (Figure ) access for these procedures with ultrasound guidance to ensure an isolated anterior wall puncture.…”
Section: Interventional Proceduresmentioning
confidence: 99%